2003
DOI: 10.1074/jbc.m205528200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Induces Cell Survival and Proliferation through the Activation of the MAPK Pathway in a Human Hormone-dependent Leukemia Cell Line, TF-1

Abstract: The tight control of proliferation, survival, and apoptosis of bone marrow progenitor cells has a major role in allowing normal hematopoiesis. A variety of cytokines, including GM-CSF 1 and IL-3, regulate viability, proliferation, differentiation, and function of hemopoietic cells (1). Hemopoietic cells undergo apoptotic cell death in the absence of growth factors, whereas an escape from this regulation may result in leukemogenesis.The human GM-CSF/IL-3-dependent myelo-erythroid cell line, TF-1, has been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 52 publications
(43 reference statements)
3
44
0
Order By: Relevance
“…It has been previously described that pharmacological modulation of Ca 2+ homeostasis by SERCA inhibitors or Ca 2+ ionophores can affect cell survival, proliferation and apoptosis in various cell types [92,93]. Furthermore, such treatments can induce or enhance cell differentiation in Friend erythroleukemia cells [94], in myeloid leukemia [95] and colon cancer [89].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously described that pharmacological modulation of Ca 2+ homeostasis by SERCA inhibitors or Ca 2+ ionophores can affect cell survival, proliferation and apoptosis in various cell types [92,93]. Furthermore, such treatments can induce or enhance cell differentiation in Friend erythroleukemia cells [94], in myeloid leukemia [95] and colon cancer [89].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, such treatments also caused a relatively low rate of dead cells. It is well known that ERK mediates cell cycle progression by activating the c-Fos transcription factor through phosphorylation of Elk-1 (51). In addition, ERK has also been shown to phosphorylate several other nuclear transcription factors such as Jun, Myc, p62TCF, and Fos, and also regulate the expression of their downstream genes (38,51,52).…”
Section: Classical Pkc Isoform(s) Are Involved In Ltdmentioning
confidence: 99%
“…4, B and C, this 1.9-fold decrease in the Camk4 Ϫ/Ϫ KLS cells is statistically significant. Several studies have shown that transcription of the pro-survival gene Bcl-2 gene requires pCREB and can be stimulated by Ca 2ϩ (27)(28)(29). Moreover, in addition to its role in cell survival, Bcl-2 has been reported to play a role in maintaining cellular quiescence (30,31).…”
Section: Surprisingly Cbp Is Significantly Reduced By 24-fold In mentioning
confidence: 99%